146 Human Interictal Epileptiform Discharges are Traveling Waves Reflecting Ictal Self-organization. (1st April 2022) - Smith, Elliot; Liou, Jyun-you; Merricks, Edward; Davis, Tyler; Thomson, Kyle; Greger, Bradley; House, Paul A.; Emerson, Ronald; Goodman, Robert R.; McKhann, Guy M.; Schevon, Catherine; Rolston, John D.
Abstract : INTRODUCTION: Interictal epileptiform discharges (IEDs), are large intermittent electrophysiological events observed between seizures in epileptic patients. While seizures are infrequent and unpredictable, IEDs are far more common, occurring several times per minute (0.67 IEDs per minute in this dataset). The relative frequency of IEDs makes them an alluring indicator of epileptogenic brain, especially when compared to more scarce and unpredictable seizures. Yet despite the relative abundance of IEDs, it remains unknown how they relate to seizures. METHODS: To better understand this relationship, we examined semi-chronic, multi-day recordings of 96-channel microelectrode arrays implanted in human epilepsy patients. These recordings—spanning single cell action potentials to local field potentials—allowed us to study the microscale spatiotemporal organization of over 45, 000 IEDs across 10 patients. We used ordinary multivariate linear regression to estimiate IED speed and direction, and vonMises Mixture models to cluster bimodal IED directions in to sub-distributions. RESULTS: These recordings showed that the majority (66.4%) of IEDs propagate across neocortex as traveling waves with a dominant direction (Hermans-Rasson Tests, all p < 10-3). IED traveling wave direction distributions were bimodal in 8 of the 10 subjects, with a median difference between sub-distributions of 178 degrees. Firing rates and voltages of IEDs in each sub distribution were not significantly different, however, the proportion of IEDs in each sub-distrbution and their speeds and directions were different among sub-distributions, and mimicked sub-distributions of ictal discharges. CONCLUSION: These results show that IEDs propagate across the surface of the brain as traveling waves, and the that their directions mimic those of discharges occuring during seizures. Furthermore, these results provide a new understanding of epileptic brian tissue, and suggest that spatial features of IEDs may be used to help diagnose and treat medically refractory epilepsy.